Application of Dass-21 to Assess the Mental Health Status of Office Employees at Oil and Gas Company - Zubir, Ainna Natasha; Amir Haziq Abdul Razak, (Progress in Engineering Application and Technology, 2026)
This study explores the mental health status of office employees at Petra Energy Berhad, focusing on depression, anxiety, and stress within the corporate oil and gas sector. While research in this industry predominantly targets offshore workers, the mental well-being of office-based employees remains underexplored. Using the Depression, Anxiety, and Stress Scale (DASS-21), the study aims to assess the severity of these mental health issues and identify correlations with sociodemographic and occupational factors. A cross-sectional design was used, with 132 office employees participating in the survey. The data were analyzed through SPSS, applying descriptive and inferential statistics.The results indicate that a significant portion of respondents reported high levels of depression (79.5%) and anxiety (67.4%), while stress was most categorized as moderate (47.0%). Sociodemographic factors such as age, gender, and education were found to influence mental health outcomes. Additionally, workload and coping strategies were identified as important factors affecting employees’ mental well-being.In conclusion, mental health challenges are prevalent among office employees in the oil and gas sector. The findings suggest the need for targeted mental health interventions, improved coping resources, and organizational support to address these issues. Organizations like Petra Energy Berhad should prioritize mental health initiatives to foster a healthier work environment and improve employee